Distribution and Clinical Significance of Lupus Anticoagulant and Anticardiolipin Antibody with Systemic Lupus Erythematosus - Barua, Anupam; Paul, Sujat; Chowdhury, MA Hasan; Rabbani, Golam; Al Hasan, Suzon; Islam, Md Nazul; Dutta, Prodip Kumar; Choudhury, MA Jalil; Alam, MN (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: Systemic lupus erythematosus; lupus anticoagulant; anticardiolipin antibody; thrombosis; neuropsychiatric manifestations; pregnancy loss; thrombocytopenia DOI: 10.3329/jcmcta.v20i1.4929 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):16-22